Indonesia Airlines' Competitive Strategies - Kumalasari, Asri (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
For business companies, making a profit is final, so there are various ways to do it, including using a fixed-target marketing strategy. As an airline company, of course we are aware of the effect of price and service, considering that the airline business is included in the luxury business category. So paying attention to aspects of price and service is a necessity in getting big profits. Therefore, this research was conducted to see the increase in the decision to use Citilink Indonesia airline from the perspective of price and service strategy. The method used is quantitative with regression analysis. The unit of analysis is Citilink airline customers, totaling 98 people with incidental sampling technique. The results of the study suggest that the service variable dominates consumer decisions in using airline services. This indicates the importance of service as a business icon. While the effect of the price variable is still below 50%. This explains that price is a factor used as a supporting influence on the service aspect, thus there will be a strengthening of consumer decisions in using Citilink Indonesia airlines by 48% (the impact value of the two variables).